Dasar-dasar Pengembangan Profesi Keguruan Kristiani: Tinjauan Landasan Filosofis dan Sosiologis - Setiawan, Yohana Yulistianita; Windarti, Maria Titik (Sekolah Tinggi Teologi Kadesi Bogor, 2024)
Education is a systematic effort to develop the abilities, attitudes, and behavior of individuals in the context of their society. Teachers, as the main implementers of formal education, play a key role in the education process. Therefore, teachers must continue to develop their abilities and skills so that they do not fall behind the times. In the context of Christian teaching, teacher professional development is based on philosophical and sociological foundations rooted in the values of faith, ethics, and social justice. This article investigates the foundations of Christian teacher professional development by outlining the philosophical and sociological foundations underpinning the practice of teaching in the context of Christian faith. The philosophical approach includes Christology, Christian epistemology, and Christian axiology, while the sociological approach emphasizes respect for diversity, education for social justice, collaboration, and participation. Through the application of these principles, Christian teachers can play a significant role in shaping students' character, values, and knowledge in accordance with the teachings of the Christian faith and the demands of the times.